THE REPRESENTATION OF CHILDREN IN LEMBAGA PERLINDUNGAN ANAK JAWA TIMUR PRINT ADVERTISEMENTS: A MULTIMODAL DISCOURSE ANALYSIS - Noorshaqienna, Eva Celya (2017)
The present study is a multimodal discourse analysis which examines the visual and verbal representation of children in Lembaga Perlindungan Anak Jawa Timur (LPA Jatim) print advertisements and the signification of the representation. This study employs descriptive qualitative approach. The data used in the present study include six print advertisements of LPA Jatim. The analysis was divided into visual and verbal analysis. The visual analysis was conducted in order to identify the visual mode by using the theory of visual grammar as proposed by Kress and van Leeuwen (2006). Meanwhile, the verbal analysis was conducted to examine the verbal mode by using transitivity system as proposed by Halliday (1994). The findings show that the children are visually represented as the core of information who are powerless and sad. Meanwhile, the verbal representation indicates that the children are portrayed as the victims of the emotional abuse who express fear and reclusiveness. These findings signify that children are represented as the ones who receive negative treatment from emotional abuse. Through the representation, the producer of the advertisements intends to persuade the viewers to take an action to fix the issue.----------Penelitian ini menggunakan analisis wacana multimodal yang menganalisis representasi anak secara verbal dan visual pada iklan cetak Lembaga Perlindungan Anak Jawa Timur (LPA Jatim) dan makna dari representasi tersebut. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data yang digunakan dalam penelitian ini adalah enam iklan cetak LPA Jatim. Terdapat dua prosedur analisis: visual dan verbal. Analisis visual dilakukan untuk menganalisis mode visual dengan menggunakan teori visual grammar yang diusulkan oleh Kress and van Leeuwen(2006). Analisis verbal dilakukan untuk menganalisis mode verbal dengan menggunakan sistem transitivity yang diusulkan oleh Halliday (1994). Temuan menunjukan bahwa anak-anak secara visual digambarkan sebagai seseorang yang lemah, sedih, dan merupakan inti dari informasi. Sementara analisis verbal menunjukan bahwa anak-anak digambarkan sebagai korban dari kekerasan emosional yang menunjukkan rasa takut dan tertutup. Temuan tersebut menandakan bahwa anak-anak digambarkan sebagai seseorang yang menerima perlakuan negatif dari kekerasan emosional. Melalui representasi tersebut, produser iklan bermaksud untuk mengajak pembaca untuk mengambil tindakan untuk memperbaiki masalah tersebut.